دور المسؤولية الاجتماعية في تحقيق الميزة التنافسية في شركات بيع الأجهزة المنزلية بأمانة العاصمة - الحميدي عبد الله راجح علي حسن; طواف عبد الخالق هادي محسن (Journal of Amran University, 2024)
The study aimed to identify the role of corporate social responsibility (CSR) in achieving competitive advantage in selling home appliance companies in the capital Municipality. It examined and analyzed the level of CSR practices in terms of: (environmental responsibility, employee responsibility, community responsibility, and customer responsibility), as well as the level of achieving competitive advantage in selling home appliance companies in the capital Municipality. The study used a descriptive-analytical method, with a questionnaire as the data collection tool. The study population consisted of all employees at middle and lower management levels in three companies in the capital city: NATCO Electronics, Middle East METCO, and Artex Trading Co., Ltd. The study employed a comprehensive census approach, surveying a total of 86 individuals at the middle and lower administrative levels of the companies under study. The study found that the level of CSR practices in the studied companies was high, and the level of competitive advantage was also high. It revealed that CSR plays a role in achieving competitive advantage in the studied companies. The study concluded with several recommendations, the most important of which are: increasing attention to CSR practices in the studied companies as an important variable that affects competitive advantage, improving the level of competitive advantage in all dimensions, and leveraging the influential relationship between CSR and competitive advantage to enhance the company's sustainability and promote positive impact on its competitive advantage.